PHOTO SHARING WEBSITES USING PERSONALIZED AND NON-PERSONALIZED IMAGE SEARCH - Dr.K.P.Kaliyamurthie, V.Dhavamani V.Shalini , Dr.K.P.Kaliyamurthie (International Journal of Engineering and Computer Science, 2017)
Increasingly developed social sharing websites, like photobucket, pixable, picasa, piczo, instagram and Kodak gallery, allow users to create, share, annotate and comment medias. Photo sharing websites helps in publishing or transferring user's photos on-line, that enables the user to share their photos with others publicl/ privately . Nowadays, there has been an increase in the photo sharing websites which allows users not only to create, share, annotate and comment multimedia contents, but also provide useful information to improve media retrieval and management. Experiments conducted on the COREL image dataset demonstrate the effectiveness and efficiency of the proposed integrated framework and the conversion strategies.